MEMAHAMI HUBUNGAN DAN KOMUNIKASI PEMIMPIN DAN BAWAHAN DALAM PERSFEKTIF AL-QUR’AN - Rahmah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
In the Qur’an, leadership is understood as a trust that carries moral and spiritual responsibilities rather than merely a formal position. It requires constructive relationships and ethical communication between leaders and subordinates. This study explores leadership relationships, the goals of leadership communication, and the implications of Qur’anic values in organizational contexts. Using a qualitative library-based approach, the research examines the Qur’an, hadith, tafsir, and relevant academic sources. The findings show that Qur’anic leadership is rooted in trust, justice, compassion, and cooperation. Leadership communication seeks to convey truth, develop shared understanding, encourage participation through consultation (shūrā), and support the moral and spiritual growth of subordinates. These values contribute to ethical and participatory leadership practices that remain relevant to contemporary management.